Endodontics and forensic personal identification: An update - Ahmed, Hany Mohamed Aly (European Journal of General Dentistry, 2017)
Dental identification of a deceased individual is a core task in forensic odontology. The accurate recording of clinical dental procedures has become more important over time because of the increasing trend of lawsuits worldwide. Previous reports have discussed the practical usefulness of endodontic evidence for human identification. Advances in endodontic imaging, root and root canal anatomy, and biomaterials have been consistently emerging in endodontic research and practice. This article provides an update on the interrelationship between endodontics and forensic personal identification.
Keywords: Anatomy; endodontics; forensic dentistry; forensic odontology; imaging